Peningkatan pemberdayaan keluarga dalam upaya pencegahan stunting melalui taman gizi di Kelurahan Sumbersari Kabupaten Jember - Kustin Kustin (Universitas Mataram, 2021)
Salah satu masalah yang dihadapi Indonesia terhadap masalah kualitas Sumber Daya Manusia (SDM) adalah masalah gizi. Masalah gizi yang dihadapi salah satunya adalah masih tinggi jumlah anak diindonesia yang tinggi badannya di bawah standart atau pendek (stunting). Stunting merupakakan salah masalah multisektoral baik dari bidang kesehatan, pertanian, ekonomi maupun sosial. Salah satu intervensi yang bisa diberikan adalah pemantauan tumbuh kembang anak, penatalaksanaan gizi kurang/buruk, promosi kesehatan dan lain sebagainya. Intervensi yang diberikan pada pengabdian masyarakat in adalah pendidikan dan pelatihan untuk meningkatkan kesadaran masyarakat akan stunting dan bahayanya, juga sosialisasi guna meningkatkan pengetahuan tentang pencegahan stunting Stunting is one of the main multisector problems in the health, agriculture, economy and social sectors. One of the interventions that can be given is management of malnutrition and health improvement. The interventions provided in this community service are education and training involving the role of the family in nutrition gardening activities around the house to provide healthy food with the nutrition awareness family program (KADARZI). This community service activity aims to increase the role and empowerment of families in efforts to prevent stunting through a nutrition garden. This family empowerment method is carried out by providing health education and socialization, land use training and making complementary foods for breast milk. This training activity was attended by 30 people. The results of the evaluation of activities from the first meeting to the last obtained the results before the training activities were that the level of knowledge was mostly lacking namely 73% and after participating in activities and training the level of knowledge increased to good knowledge of 81%. This KADARZI training is an effort to help mothers save on shopping expenses for purchasing vegetables, this is because it has been fulfilled by planting vegetables around their home land.